2018
DOI: 10.1016/j.jneuroim.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA miR-21-5p, miR-150-5p and miR-30e-5p correlate with clinical status in late onset myasthenia gravis

Abstract: There are no biomarkers for late onset myasthenia gravis (LOMG; onset >50 years). We evaluated circulating microRNA in a discovery cohort of 4 LOMG patients and 4 healthy controls and in a prospective diagnostic validation cohort of 73 LOMG patients (48 male) with longitudinal follow-up samples. In immunosuppression naïve patients, levels of miRNAs miR-150-5p, miR-21-5p and miR-30e-5p decreased in parallel with clinical improvement after initiation of immunosuppression and their levels positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This study found a steady decline in clinical MGC score at and after 1-year follow-up, which correlated with reduced levels of miR-150-5p, miR-21-5p, and miR-30e-5p (56; Figure 1), related to immunosuppression initiation after onset. Intriguingly, patients with generalized LOMG had higher levels of miR-150-5p and miR-21-5p than those with ocular LOMG (56). None of these miRNAs correlated with the AChR antibody levels, hence supporting the previous studies (48,49,51).…”
Section: Late-onset Mgsupporting
confidence: 78%
See 3 more Smart Citations
“…This study found a steady decline in clinical MGC score at and after 1-year follow-up, which correlated with reduced levels of miR-150-5p, miR-21-5p, and miR-30e-5p (56; Figure 1), related to immunosuppression initiation after onset. Intriguingly, patients with generalized LOMG had higher levels of miR-150-5p and miR-21-5p than those with ocular LOMG (56). None of these miRNAs correlated with the AChR antibody levels, hence supporting the previous studies (48,49,51).…”
Section: Late-onset Mgsupporting
confidence: 78%
“…Interestingly, the data from another cohort study on circulating miRNA in LOMG did not overlap regarding the results from the study by Nogales-Gadea (54). The discrepancies between these two studies (54,56) could be explained by the differences in the LOMG patient cohort numbers as well as their immunosuppressive treatment status.…”
Section: Late-onset Mgmentioning
confidence: 89%
See 2 more Smart Citations
“…In AChR+ MG, the miRNAs miR-150-5p, and miR-21-5p were upregulated compared to healthy controls and these levels were also lower in patients treated with immunosuppression as compared to immunosuppression naïve patients (5,6). In addition to miR-150-5p and miR-21-5p, levels of miR-30e-5p were found to be upregulated in late onset AChR+ MG patients and expression of these miRNAs correlated with disease course (7). Interestingly, miR-30e-5p levels were found to be higher in patients with ocular AChR+ MG who later develop generalized MG as compared to those that remain ocular.…”
Section: Introductionmentioning
confidence: 92%